2011
DOI: 10.1016/j.cell.2011.01.020
|View full text |Cite|
|
Sign up to set email alerts
|

Role for Dpy-30 in ES Cell-Fate Specification by Regulation of H3K4 Methylation within Bivalent Domains

Abstract: Summary Histone H3K4 methylation is associated with active genes and, along with H3K27 methylation, is part of a bivalent chromatin mark that typifies poised developmental genes in embryonic stem cells (ESCs). However, its functional roles in ESC maintenance and differentiation are not established. Here we show that mammalian Dpy-30, a core subunit of the SET1/MLL histone methyltransferase complexes, modulates H3K4 methylation in vitro, and directly regulates chromosomal H3K4 trimethylation (H3K4me3) throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
235
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(262 citation statements)
references
References 49 publications
24
235
1
2
Order By: Relevance
“…Analysis of our Ash2l ChIP-seq data and previously published studies has revealed genome-wide co-occupancy of Ash2l, Rbbp5, Dpy-30, as well as histone H3K4me3 on ES cell chromatin (55,61). These observations underscore their importance for establishing and maintaining an open chromatin in ES cells, and are consistent with Ash2l/Rbbp5/Dpy-30 forming a core complex that is required for establishing and maintaining H3K4me3 (37,61).…”
Section: Discussionsupporting
confidence: 69%
“…Analysis of our Ash2l ChIP-seq data and previously published studies has revealed genome-wide co-occupancy of Ash2l, Rbbp5, Dpy-30, as well as histone H3K4me3 on ES cell chromatin (55,61). These observations underscore their importance for establishing and maintaining an open chromatin in ES cells, and are consistent with Ash2l/Rbbp5/Dpy-30 forming a core complex that is required for establishing and maintaining H3K4me3 (37,61).…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, Wdr5, a shared component of the Kat8-containing complex and the MLL complex catalyzing H3K4 methylation [56], displays a phenotype similar to that of Kat8 when depleted in ESCs [57]. Given that Dpy30, another MLL complex component regulating H3K4 methylation, is dispensable for ESC self-renewal [58], it seems likely that the Kat8-containing complex mediates the Wdr5 function. In support of this notion, the recruitment of Wdr5 to its target loci, including key pluripotency genes, depends on Kat8 [25].…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Enzymes depositing or removing H3K4 methylation have been shown to play important roles in ESCs. Dpy30, a component of the MLL histone methyltransferase (HMT) complex, is required for ESCs to commit to the neural lineage [58], indicating that H3K4me3 deposited by MLL is crucial for maintaining differentiation potential in ESCs. Deficiency in Kdm1a, an H3K4me2/1-specific demethylase, results in spontaneous differentiation of human ESCs [68].…”
Section: H3k4 Methylationmentioning
confidence: 99%
“…The interaction between Ash2L and RbBP5 is essential for MLL1 complex integrity and activity regulation [2,5]. The Ash2L-DPY30 interaction was recently reported to be important for the regulation of nucleosomal H3K4 trimethylation and the differentiation potential of embryonic stem cells [6]. Ash2L protein adopts a modular configuration.…”
Section: Dear Editormentioning
confidence: 99%